How to wow : proven strategies for presenting your ideas, persuading your audience, and perfecting your image - Jones, Frances Cole (Ballantine Books, 2008)
"In today's fast-paced world, where an elevator ride with your CEO can turn into an impromptu meeting, your lunch date can become a job interview, and your conversation at a cocktail party may be a preamble to a potential business merger, knowing how to market yourself in any situation is vital. Corporate coach Frances Cole Jones has helped numerous CEOs, celebrities, and public personalities present their best selves on camera and onstage, in boardrooms and in person. Now, in her new book, How to Wow, she shares her strategies for making your mark in business and in life." "Every encounter, Jones believes, provides you with an opportunity to positively influence colleagues, employers, neighbors - even competitors. Not only your words, but your tone of voice and your body language speak volumes. The question, however, is: Are they working together to say what you want them to, as effectively as possible?".